Dietary supplements for improving body composition and reducing body weight: Where is the evidence? - Manore, M. M. (International Journal of Sport Nutrition and Exercise Metabolism, 2012)
Weight-loss supplements typically fall into 1 of 4 categories depending on their hypothesized mechanism of action: products that block the absorption of fat or carbohydrate, stimulants that increase thermogenesis, products that change metabolism and improve body composition, and products that suppress appetite or give a sense of fullness. Each category is reviewed, and an overview of the current science related to their effectiveness is presented. While some weight-loss supplements produce modest effects (2 kg), especially in the long term. Some foods or supplements such as green tea, fiber, and calcium supplements or dairy products may complement a healthy lifestyle to produce small weight losses or prevent weight gain over time. Weight-loss supplements containing metabolic stimulants (e.g., caffeine, ephedra, synephrine) are most likely to produce adverse side effects and should be avoided.